Microstructure evolution and the mechanical properties of in-situ Ti2AlCw-NbC@TiBx/TiAlNb composite with high performance. (1st April 2022) - Cui, Sen; Cui, Chunxiang; Yang, Shichao; Liu, Shuangjin
Abstract: This manuscript reports an innovative preparation method of TiAl matrix composites. The mixed AlNb powder and B4 C powder were put into TiAlNb alloy melt after ball milling. With the help of the reaction in AlNb/B4 C powders and the in-situ reaction of various elements in TiAlNb alloy melt, hybrid Ti2 AlCw and NbC@TiBx core-shell structure with high dispersion and good interface bonding were synthesized and introduced into TiAlNb alloy. The analysis shows that the NbC/TiBX of the core-shell structure was based on the in-situ reaction on the NbC substrate obtained in high-energy ball milling and was formed by the in situ reaction in the TiAlNb melt. The NbC@TiBx structure and the in-situ Ti2 AlC whiskers both have excellent interfacial bonding with TiAl matrix. In this TiAlNb composite with dual-scale reinforcements, the combination of multiple strengthening/toughening mechanisms improves the mechanical properties of TiAlNb alloy matrix. The in-situ Ti2 AlCw and NbC@TiBx hybrid reinforced TiAlNb composite was prepared successfully. Room compression tests show that the fracture stress and strain of the composite are increased from 1548 MPa, 20.6% to 2678 MPa, 29.1%. And the high temperature compression tests (at 1073 K) show that the fracture stress and strain of the alloy are increased from 641 MPa, 23.4% to 1012 MPa, 35.9%.